In vitro characterization of intra-generic inhibition of growth in Salmonella typhimurium - Berchieri, A. [UNESP]; Barrow, P. A. [UNESP] (Microbiology Society, 1991)
The intra-generic inhibition of bacterial growth observed previously in vivo and in vitro with strains of Salmonella, Citrobacter and E. coli was studied in vitro using S. typhimurium strain F98. There was complete inhibition of multiplication of S. typhimurium when it was added to stationary-phase broth cultures of different Salmonella serotypes, but only partial inhibition when added to broth cultures of E. coli. The degree of inhibition between different mutants of F98 was affected by the numbers of bacteria of the inhibiting strain, but this was not the only factor, since exponential-phase bacterial cells were less inhibitory than stationary-phase cells. The inhibitory effect was produced at temperatures between 20°C and 40°C. The complete inhibition of growth observed between F98 mutants was abolished by ampicillin, rifampicin and streptomycin, but not by nalidixic acid. Inhibition was also prevented by separating the two cultures by a dialysis membrane. A Tnpho A Insertion mutant of F98 was produced which did not show inhibition in vitro but was still inhibitory in vivo. It is suggested that this complete inhibition of bacterial multiplication between organisms of the same genus, which is greater than that produced between organisms from different genera, is mediated by a cell surface protein.
Keywords: ampicillin; cell surface protein; nalidixic acid; rifampicin; streptomycin; bacterial growth; bacterium mutant; dialysis membrane; growth inhibition; nonhuman; priority journal; salmonella typhimurium; Animal; Antibiotics; Blotting, Southern; Chickens; Colony Count, Microbial; Dialysis; Drug Resistance, Microbial; Mutation; Salmonella typhimurium; Support, Non-U.S. Gov't; Temperature; Time Factors; Bacteria (microorganisms); Citrobacter; Typhimurium